Effects of partial or total replacement of corn cracked grain with high concentrations of crude glycerin on rumen metabolism of crossbred sheep - Branco van Cleef, Eric Haydt Castello [UNESP] (2018)
Crude glycerin, a by-product of the biodiesel industry, has been used as a strategic ingredient in intensive ruminant production systems, mainly in substitution of starch-rich ingredients. The present study was performed to evaluate the effects of the inclusion of up to 30% of crude glycerin in diets for feedlot sheep, on ruminal parameters, such as pH, NH3-N and volatile fatty acids concentrations, in situ degradability, as well as in vitro greenhouse gas production and in vitro digestibility. Eight ruminally-cannulated male Santa Ines x Dorper sheep (64.5 +/- 8.5 kg) were distributed in a replicated 4 x 4 Latin square design. The experimental diets contained 0, 10, 20 or 30% of crude glycerin and were labeled as GO, G10, G20 and G30, respectively. The crude glycerin totally replaced the corn cracked grain in treatment G30. The inclusion of crude glycerin in the diets tended to promote a quadratic effect in DMI, with greater values observed for treatments G10 and G20. Crude glycerin tended to increase the ruminal pH and NH3-N, but linearly reduced the total molar concentration of WA, acetic, butyric, isobutyric and isovaleric acids. Treatments linearly increased in vitro DM digestibility of diets and linearly reduced NDF digestibility. The inclusion of crude glycerin in the diets linearly decreased the in vitro total gas and CO2 production (mL/g degraded) and tented to reduce CH4 (mL/g degraded). A linear increase of soluble fraction in water (a) of the diets was observed with the increasing inclusion of crude glycerin. The insoluble but potentially degradable fraction (b) of DM and NDF of the diets were linearly decreased and increased, respectively. The potential ruminal degradation of the diets was markedly and linearly increased with the increasing inclusion of the by-product. The replacement of corn cracked grain by crude glycerin (up to 30% DM) changes rumen fermentation parameters, decreasing VFA production, in vitro total gas production and CH4. Additionally, the potential and effective degradation as well as in vitro DM digestibility of diets are improved while fiber digestibility is impaired.